Capital Structure and Technology Investment on Profit Growth: The Moderating Role of Operational Efficiency in ASEAN Islamic Banks - Fahmi Ilham Fadjar; Ulfi Kartika Oktaviana (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
This study examines the effect of capital structure and technology investment, proxied by non-interest expenses, on profit growth, with operational efficiency serving as a moderating variable in ASEAN Islamic banks. Unlike previous studies that primarily examine operational efficiency as a direct determinant of financial performance, this study evaluates its moderating role while employing non-interest expenses as an operational proxy for technology investment in the ASEAN Islamic banking context. Panel data from 26 Islamic banks during 2020–2024 were analyzed using the Random Effects Model (REM) and Moderated Regression Analysis (MRA). The results indicate that capital structure has no significant effect on profit growth (β = –28.942; p = 0.454), whereas technology investment has a positive and significant effect (β = 75.824; p = 0.004). Operational efficiency does not significantly moderate the relationship between capital structure and profit growth (β = 13.701; p = 0.173), but it significantly moderates the relationship between technology investment and profit growth through a negative interaction effect (β = –51.815; p = 0.037), indicating that the profitability benefits of technology investment depend on efficient operational cost management. These findings provide empirical evidence that technology investment contributes to sustainable profit growth only when supported by operational efficiency, thereby extending the application of X-Efficiency Theory in explaining financial performance within ASEAN Islamic banks.